The prevalence and infection rates of amphistome species in intermediate snail hosts: a systematic review and meta-analysis - Nyagura, Ignore; Malatji, Mokgadi Pulane; Mukaratirwa, Samson (Frontiers in Veterinary Science, 2024)
The systematic review and meta-analysis was conducted to determine the prevalence and infection rate estimates of natural and experimental infections of amphistome species in snail intermediate hosts from different continents. A search of peer-reviewed literature on natural and experimental infection of freshwater snails with amphistome species was conducted from four electronic databases from 1984 to 2023. Prevalence and/or infection rates estimates were based on 36 eligible peer-reviewed articles which met the inclusion criteria and reported on natural and experimental infections of amphistome species in freshwater snails. Results showed that a total of 167081 snail species from the peer-reviewed articles were examined for natural infections and 7659 for experimental infections. The overall pooled prevalence of amphistome infections from naturally infected snails was 2% (95% CI: 0 to 4), compared to 40% (95% CI: 18 to 64) infection rate on experimental infections. The highest pooled prevalence from natural infection was recorded in Europe 3% (95% CI: 1-7%). The highest overall prevalence of naturally infected amphistome was 6% (95% CI: 0-20%) for Paramphistomum epiclitum. The Americas had the highest pooled prevalence of experimental amphistome infecRon among freshwater snails (66%; 95% CI: 26-96%). The highest pooled infection rate of 65% (95% CI: 12-100%) was recorded for P. cervi in experimental infections. Galba truncatula was the only snail that qualified for meta-analysis for natural infection with Calicophoron daubneyi, with the pooled prevalence of 3% (95% CI: 1-8%). Galba truncatula infected with C. daubneyi and P. cervi, and Bulinus tropicus infected with C. microbothrium in the experimental infecRon qualified for the meta-analysis, with the